“AN EMPIRICAL ANALYSIS ON DEFINING FRAMEWORK ON QUALITY OF HIGHER EDUCATION IN INDIA IN SPECIAL REFERENCE TO RAJASTHAN” (International Journal of Food and Nutritional Sciences, 2022)
The education system has faced many huddles, it also has many opportunities to overcome these obstacles and improve higher education. Since India exports most of the highly skilled labour to different nations, it is simple for India to move from being a developing country to a developed one. However, the education system currently faces a number of issues that are cause for concern, including access, equity, and relevance in financing and management, reorientation of programmes to place an emphasis on health consciousness,Together with the evaluation of institutions and their accreditation, higher education's values, ethics, and quality are considered. The current study aims to identify opportunities and challenges in India's higher education system. These issues are crucial for the nation because it is currently working to create a knowledge-based information society fit for the 21st century using higher education as a potent tool.